Resposta :
Explicação passo-a-passo:
e)
x/6 = 11
X = 11 . 6
X = 66
F
X/7 = 9
X = 9 . 7
X = 54
G
X/8 = 8
X = 8 . 8
X = 64
H
X/9 = 12
X = 12 . 9
X = 108
I
X/2 = 1
X = 1 . 2
X = 2
J
X/6 = 7
X = 7 . 6
X = 42
e)
[tex] \frac{x}{6} = 11[/tex]
[tex]x = 11 \times 6[/tex]
[tex]x = 66[/tex]
[tex]f) \frac{x}{7} = 9 \\ x = 9 \times 7 \\ x = 63[/tex]
g)
[tex] \frac{x}{8 } = 8 \\ x = 8 \times 8 \\ x = 64[/tex]
H)
[tex] \frac{x}{9} = 12[/tex]
[tex]x = 12 \times 9[/tex]
[tex]x = 108[/tex]
I)
[tex] \frac{x}{2} = 1 \\ x = 2 \times 1 \\ x = 2[/tex]
J)
[tex] \frac{x}{6} = 7[/tex]
[tex]x = 7 \times 6[/tex]
[tex]x = 42[/tex]